LAMA PENYIMPANAN DAN PEMANFAATAN LARUTAN DAUN SIRIH (Paper Betle Linn) SEBAGAI DESINFEKTAN ALAMI TERHADAP DAYA HIDUP EMBRIO, DAYA TETAS SERTA BOBOT TETAS TELUR PUYUH - Izzul Islam, Jihad Izzul Islam; Hafid, Harapin; Indi, Amiluddin (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2019)
ABSTRACTThis research was conducted with the aim to determine the effect of storage time and concentration ofsolution of betel leaf as a natural disinfectant in quail hatching eggs. This study used a factorialCompletely Randomized Design (CRD) with 2 factors, namely factor A consisted of ole (storage time 5and 7 days), factor B consisted of (dyeing betel leaf solution with treatment P0 = Without treatment, P1 =100 grams of betel leaf + 500 ml of water, P2 = 100 grams of betel leaf + 1000 ml of water, and P3 = 100 grams of betel leaf + 1500 ml of water). The material used in this study was 320 eggs of quail and 2 unitsof hatchery with a capacity of 200 eggs. The results of this study indicate that the interaction of treatmentbetween factor A and factor B, as well as the treatment of each individual, did not have an effect on thesurvival of the embryo, hatchability and the hatch weight of quail eggs.Keywords: Embryo, hatchability, hatch weight,betel leaf, quail.Â